Set of games and activities on roller skis for young skiers aged 12-14 - Korbelár, T.; Suchý, J. (Journal of Outdoor Activities, 2018)
Aim of Study: To create a set of games and activities on rollers skis for young cross-country skiers aged between 12 and 14 years and have them checked by experts. Material and Methods: The first method used in this work was an analysis of the available Czech and international documents about games and activities. Then a set of games and activities was assembled, which was customised for roller ski training. Furthermore, the collection of roller skis games and activities was vetted with the help of a panel of experts composed of experienced and licensed cross-country ski trainers and cross-country ski experts. An unstructured interview was conducted with them followed by a discussion about each game and activity. Results: In the first part there is a chapter about the equipment used in the set we created. The main part consists of a customised and tested collection of roller ski games and activities for young cross-country skiers aged between 12 and 14 years. The panel of experts went through them and added their ideas and suggestions to specific games and activities in the form tips and suggestion. At the end of the final part a new chapter dividing up the collection was created as a result of discussion with the panel of experts. The division was made according to three main viewpoints, which are safety, space and the number of competitors.